The effect of teaching style on affective and cognitive motivation in physical education - Nur Azis Rohmansyah; Sri Mawarti; Ashira Hiruntrakul (Jurnal Keolahragaan, 2022)
The theory of accomplishment-generating motivation only adopts a social cognitive method to research behavior and motivation in sports education settings, illuminating how achievement goal theory is useful for anticipating and explaining beliefs, reactions, and behaviors in achievement settings. This study aimed to investigate how different teaching approaches teacher-centered and student-centered affected the emotional and cognitive motivational responses of students during physical education classes. Using several Mosston and Ashworth teaching methods, including command style, reciprocal style, and guided exploration style, four teachers instructed 92 students. To evaluate teaching style, the Ames coding system was employed. In this inquiry, a strategy of mixed methods was used. By adjusting the work design, authority, recognition, grouping, assessment, and class time structure, the video data was evaluated. The hard disk software enables the recording of audio and video recordings as well as the real-time analysis of information acquired from course observations in physical education. An ANOVA analysis with the Bonferroni correction method was carried out to prevent Type 1 errors, and it produced an alpha level of 0.002 as a result. The command style, reciprocal style, and guided style all performed significantly differently, according to the Tukey test, in terms of total mastery and teaching style effectiveness. According to the findings, guided and reciprocal discovery styles were more effective than command approaches in terms of student mastery, less focused teacher behavior, and cognitive and emotional responses.